Analisis Implementasi Program Kegiatan Mengajar, Administrasi Sekolah dan Mengikuti Kegiatan Sekolah di SD Negeri 01 Sebetung Menyala - Hendrikus Torimtubun; Melania Jesica (Lembaga Pengembangan Kinerja Dosen, 2025)
this activity aims to analyze the implementation of the Teaching Activity Program, School Administration and Participating in the School Activities at State Elementary School 01 Sebetung Menyala. This research was conducted at State Elementary School 01 Sebetung Menyala. The researcher used a descriptive qualitative approach. This research was conducted from September 02, 2024 to January 10, 2025. The subject in this study were students from class I to VI at State Elementary School 01 Sebetung Menyala. The data sources in this study were primary data sources and sekuder data sources. Primary data sources, namely the author, can be obtained from the implementation of Field Experience Practices Program at State Elementary School 01 Sebetung Menyala and sekuder data source, namely obtained from a reference source of various research journals that comply with this research. Data collection techniques used are observations directly with the principals to see each corner of the school and documentation by taking several photos used as evidence. The approach method used on the implementation of this Field Experience Practice program is a direct empowerment method through the stages that have been compiled by the Field Experience Practices committee. The result that this program has a positive impact on students, teachers, and schools. This is indicated by the fact that students participate in the learning given then show better literacy levels and numeracy.